Answer:
option C
Step-by-step explanation:
We will call :
A=(-5, -1) B=(-2, -1) C=(-3, -4) D= (-3, -4)
Perimeter= 2*AB+2BC
Where AB= [tex]\sqrt{(-5+2)^{2} +(-1+1)^{2} } = \sqrt{9} =3\\[/tex]
BC =[tex]\sqrt{(-2+3)^{2} +(-1+4)^{2} } = \sqrt{10} =3.16\\[/tex]
So We have:
Perimeter=2*3+2*3.16= 12.32
Answer:
C.
Step-by-step explanation:
MARKING BRAINLIEST!!! Please help..
Karen is trying to choose a cellphone plan. Company J charges a subscription fee of $30 per month plus $1 per hour of use.
Company K charges no monthly fee, but charges $3 for every hour of use. Karen made this graph to compare the prices of the two plans....
The lines for company J and company K cross a point.
The coordinate (30,60) is the point at which company J and company K cost the same. What does the point (30,60) mean? (Hint: What is being graphed on the x-axis?
What is being graphed on the Y-axis?).
If Karen used her cell phone for less than 30 hours a month, which company should Karen choose? Why?
IF Karen uses her cell phone for more than 30 hours a month which company should she use? Why?
1. 12 mph, 24 miles
2. m=4, y=22
3.15/1, $1500
4. x=30 y=60, k cheaper, j cheaper
In △ABC, m∠A=16°, m∠B=49°, and a=4. Find c to the nearest tenth.
Answer:
c=13.2 units
Step-by-step explanation:
step 1
Find the measure of angle C
Remember that the sum of the internal angles of a triangle must be equal to 180 degrees
so
A+B+C=180°
substitute the given values
16°+49°+C=180°
65°+C=180°
C=180°-65°=115°
step 2
Find the measure of c
Applying the law of sines
c/sin(C)=a/sin(A)
substitute the given values and solve for c
c/sin(115°)=4/sin(16°)
c=4(sin(115°))/sin(16°)
c=13.2 units
12.03,1.2,12.3,1.203,12.301 order least to greatest
Answer:
1,2, 1,203, 12,03, 12,3, 12,301
Step-by-step explanation:
1,2 → 1,200
1,203
12,3 → 12,300
12,301
I am joyous to assist you anytime.
Ordered from least to greatest:
1.21.20312.0312.312.301Johnny had $800.00, sue had $500.00, and Doug had $300.00.who had the most
Answer:
Johnny
Step-by-step explanation:
I don't think you put the whole question out
If C is the midpoint of segment AB and AB = 20, what is AC?
AB= 20 and AB is the full line.
We will have to divide the length of the segment by 2 to find AC.
20/2= 10
AC is 10 units. Hope this helps!
Answer: the answer is: AC= 10
Step-by-step explanation:
you can imagine a line that represents AB with 20cm of large and the midline is located in the middle of this line; this means that AC is the half of AB
So in number=
[tex]AC= AB/2[/tex]
replacin [tex]AB[/tex]
[tex]AC= 20/2[/tex]
[tex]AC=10[/tex]
Graph the line with slope -1/3 and y-intercept-3.
Answer:
The graph in the attached figure
Step-by-step explanation:
we know that
The equation of the line into slope intercept form is equal to
[tex]y=mx+b[/tex]
where
m is the slope
b is the y-intercept
In this problem we have
[tex]m=-\frac{1}{3}[/tex]
[tex]b=-3[/tex]
substitute
[tex]y=-\frac{1}{3}x-3[/tex]
To graph the line find out the intercepts
Find the y-intercept
The y-intercept is the value of y when the value of x is equal to zero
so
For x=0
[tex]y=-\frac{1}{3}(0)-3=-3[/tex]
The y-intercept is the point (0,-3) -----> is a given value
Find the x-intercept
The x-intercept is the value of x when the value of y is equal to zero
so
For y=0
[tex]0=-\frac{1}{3}x-3[/tex]
[tex]x=-9[/tex]
The x-intercept is the point (-9,0)
Plot the intercepts and join the points to graph the line
see the attached figure
To graph the line with a slope of -1/3 and a y-intercept of -3, plot the y-intercept at (0, -3) and use the slope to find additional points. Connect the points to graph the line.
Explanation:To graph the line with a slope of -1/3 and a y-intercept of -3, we can start by plotting the y-intercept at the point (0, -3). Then, using the slope, we can find additional points on the line. Given that the slope is -1/3, we can move down 1 unit and to the right 3 units from the y-intercept to find the next point. We can continue this process to find more points and then connect them to graph the line.
Learn more about Graphing a line with slope and y-intercept here:https://brainly.com/question/35469586
#SPJ3
is 42 a multiple of 7
Answer:
yes
Step-by-step explanation:
7 * 6 = 42
Please help me thank you sooo much
Answer:
Step-by-step explanation:
Firstly you must understand you want to get the value of y.
So put in values into equation which make x.
To understand here lets look at y = 0
if y is to be 0 then x is 3.
If we substitute this value into equation (B) we get the result.
Now we have identified our answer, all is left is to substitute all other values of x and see if y are true.
So , we can see B is the answer
Answer: B
Step-by-step explanation:
The answer has to be either A, or B, because when x input is negative, the y input is positive. Visa versa.
Then just input x and y into the equation to see which answer is correct.
First let’s do A: 12=-2(-3)-6
12=6-6
12 doesn’t equal 0, so A is incorrect
So then B is the obvious solution, but let’s solve it to make sure: 12=-2(-3)+6
12=6+6
This equation is true, so the answer is B
Sat math. Only one question. I am not sure of the answer
Answer:
8
Step-by-step explanation:
To find Y, find X first. Multiply 2 by W (3) which is 6, and divide by 3, which gives us X=2. The inequality W+Z=X+Y substituted is 10=2+Y. Subtract 2 from 10 and you get Y=8
Answer:
13) 8
14) 2X or 4W/3 (depending on what the choices are)
Step-by-step explanation:
So I'm using the box given:
If then
W X W+Z=X+Y and 2W=3X
Y Z
13)
3 X 3+7=X+Y and 2*3=3*X
Y 7
To get W,X,Y, and Z I compared it to the first lay out and then replace the other W's,X's,Y's, and Z's.
So we have 3+7=X+Y which means 10=X+Y.
We also have 2*3=3*X which means 2=X (I divided both sides by 3).
If X=2 then 10=X+Y gives us 10=2+Y.
10=2+Y can be solved by subtracting 2 on both sides:
8=Y
Y=8
14)
W X W+W=X+Y and 2W=3X
Y W
So W+W=X+Y means 2W=X+Y
We are also given 2W=3X which means by substitution into the first equation we get 3X=X+Y.
3X=X+Y can be solved by subtracting X on both sides:
2X=Y
We can also write Y in terms of W.
We have 2W=3X so that means X=2W/3 (I divided both sides by 3)
Now I'm going to replace X in 2X=Y with (2W/3) giving me:
2(2W/3)=Y
4W/3=Y
find the value of k for which the following system of equations has a unique solutions 1 . kx +2y= 5 , 3x+y=1
Answer:
If you choose any value for k other than 6, that will be give you the one solution.
If k=6, you have no solutions because the lines will be parallel.
Step-by-step explanation:
We are going to put each of this in y=mx+b where m is the slope and b is the y-intercept.
kx+2y=5
Subtract kx on both sides:
2y=-kx+5
Divide both sides by 2:
y=(-k/2)x+(5/2)
The slope is -k/2 and the y-intercept is 5/2
3x+y=1
Subtract 3x on both sides:
y=-3x+1
The slope is -3 and the y-intercept is 1.
We want the system to have one solution so we want the slopes to be difference.
So we don't want (-k/2)=(-3).
Multiply both sides by -2: k=6.
We won't want k to be 6.
Create an equivalent system of equations using the sum of the system and the first equation
-3x + y = 12
x + 3y = 6
A.-3x + y = 12
- 2x + 4y = 18
B.-3x+y=12
-3x + 4y = 18
C -3x+y = 12
X + 4y = 18
D.-3x+y=12
-2x + 4y = 6
Answer:
[tex]\large\boxed{A.\ \left\{\begin{array}{ccc}-3x+y=12\\-2x+4y=18\end{array}\right}[/tex]
Step-by-step explanation:
[tex]\underline{+\left\{\begin{array}{ccc}-3x+y=12\\x+3y=6\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad-2x+4y=18\\\\\text{therefore}\\\\\left\{\begin{array}{ccc}-3x+y=12\\-2x+4y=18\end{array}\right[/tex]
Using the equation of the sum of the system of equations and the first equation of the system, the equivalent system of equations is:
-3x + y = 12
-2x + 4y = 18
(Option A)
Given the system of equations:
-3x + y = 12 ---> Eqn. 1 x + 3y = 6 ---> Eqn. 2Add Eqn. 1 and Eqn. 2 together:
-3x + y = 12
x + 3y = 6 (ADD)
-2x + 4y = 18
Therefore, using the equation of the sum of the system of equations and the first equation of the system, the equivalent system of equations is:
-3x + y = 12
-2x + 4y = 18
(Option A)
Learn more about equivalent system of equations on:
https://brainly.com/question/1869465
x + 2y = 5 3x + 5y = 14 Solve the system of equations. (3, 1) (7, -1)
Answer:
{x,y} = {3,1}
Step-by-step explanation:
// Solve equation [1] for the variable x
[1] x = -2y + 5
// Plug this in for variable x in equation [2]
[2] 3•(-2y+5) + 5y = 14
[2] - y = -1
// Solve equation [2] for the variable y
[2] y = 1
// By now we know this much :
x = -2y+5
y = 1
// Use the y value to solve for x
x = -2(1)+5 = 3
Solution :
{x,y} = {3,1}
For this case we have the following system of equations:
[tex]x + 2y = 5\\3x + 5y = 14[/tex]
To solve, we multiply the first equation by -3:
[tex]-3x-6y = -15[/tex]
We add the equations:
[tex]-3x + 3x-6y + 5y = 14-15\\-y = -1\\y = 1[/tex]
We look for the value of the variable "x":
[tex]x + 2 (1) = 5\\x + 2 = 5\\x = 5-2\\x = 3[/tex]
Thus, the solution of the system is (3,1)
Answer:
(3,1)
GCF Problem Set A
GCF (16,24)
GCF (15, 45, 60)
Answer:
8
15
Step-by-step explanation:
To find the GCF of numbers, first find the prime factorizations of the numbers. The GCF is the product of common factors with lowest exponent.
GCF (16, 24)
16 = 2^4
24 = 2^3 * 3
GCF = 2^3 = 8
GCF (15, 45, 60)
15 = 3 * 5
45 = 3^3 * 5
60 = 2^2 * 3 * 5
GCF = 3 * 5 = 15
Answer:
A=8, B= 15
Step-by-step explanation:
Solve -2/3 x > 8 or -2/3x <4
I doubt it says "or". It's probably an and.
[tex]\dfrac{-2}{3}x > 8\wedge\dfrac{-2}{3x} < 4[/tex]
[tex]-2x > 24\wedge3x < \dfrac{4}{-2}[/tex]
[tex]x > -12\wedge x < -\dfrac{2}{3}[/tex]
[tex]\Rightarrow\boxed{-12 < x < -\dfrac{2}{3}}[/tex]
[tex]\Rightarrow\boxed{x\in(-12,-\dfrac{2}{3})}
[/tex]
Hope this helps.
r3t40
Answer:
{x | x < -12 or x > -6}
Geometry question
I got it right but I didn’t incorporate the 105
Was I supposed to ?
Answer:
See below.
Step-by-step explanation:
You didn't need to.
The angle adjacent to angle x = 45 degrees (alternate interior angle to the angle marked 45).
So x = 180 - 45 = 135 degrees.
Answer:
C. 135
Step-by-step explanation:
In the figure above, line M is parallel to line N. The value of x is 135.
x = 180 - 45 = 135
Sn=7k=1Σ[1+ (k-1)(2)]
Answer:
49
Step-by-step explanation:
I think I have read this right!
You let me know if you did not mean to write the following:
[tex]\sum_{k=1}^{7}(1+(k-1)(2)[/tex]
Alright so the lower limit is 1 and the upper limit is 7.
All this means is we are going to use the expression 1+(k-1)(2) and evaluate it for each natural number between k=1 and k=7 and at both k=1 and k=7.
The sigma thing means we add those results.
So let's start.
Evaluating the expression at k=1: 1+(1-1)(2)=1+(0)(2)=1+0=1.
Evaluating the expression at k=2: 1+(2-1)(2)=1+(1)(2)=1+2=3.
Evaluating the expression at k=3: 1+(3-1)(2)=1+(2)(2)=1+4=5.
Evaluating the expression at k=4: 1+(4-1)(2)=1+(3)(2)=1+6=7.
Evaluating the expression at k=5: 1+(5-1)(2)=1+(4)(2)=1+8=9.
Evaluating the expression at k=6: 1+(6-1)(2)=1+(5)(2)=1+10=11.
Evaluating the expression at k=7: 1+(7-1)(2)=1+(6)(2)=1+12=13.
Now for the adding!
1+3+5+7+9+11+13
4+ 12+ 20+13
16+ 33
49
Solve x2 - 8x - 9 = 0.
Rewrite the equation so that it is of the form
x2 + bx = c.
Answer:
I just got done doing this. Full answers to all 4 problems are down below. All correct answers are bolded.
Step-by-step explanation:
First problem: x2 + -8 x = 9
Add 16 to each side x2 – 8x = 9 to complete the square.
Now that you have x² - 8x + 16 = 9 + 16, apply the square root property to the equation. Answer: (x – 4)² = 25
Choose the solutions to the quadratic equation x2 – 8x – 9 = 0. Answer: -1, 9
The equation x² - 8x - 9 = 0 can be written as x² +(-8x) = 9 which is of the form x² + bx = c where,
b = -8
c = 9
What are equations?An equation is a mathematical statement which equate two algebraic expressions. An equation has an equal to (=) sign in between the expression.
How to rewrite the given equation in the given form?The given equation is
x² - 8x - 9 = 0.
⇒ x² - 8x = 9
⇒ x² +(-8x) = 9
So the given equation is written of the form x² + bx = c, where,
b = -8
c = 9
Find more about "Equations" here : https://brainly.com/question/1833682
#SPJ2
What is the slope of a line whose equation
is 7x - 5y = 10?
Help me please !
Answer:
7/5
Step-by-step explanation:
Slope intercept form is y=mx+b. It is called that because it tells us the slope,m, and the y-intercept, b.
So we can solve your given equation to find m the slope.
7x-5y=10
Subtract 7x on both sides:
-5y=-7x+10
Divide both sides by -5
y=(-7/-5)x+(10/-5)
Simplify:
y=(7/5)x+-2
m=7/5 so 7/5 is the slope.
A company borrowed 25,000 at 3.5 % and was charged 2,625 in interest. How long was it before the company repaid the loan?
[tex]\bf ~~~~~~ \textit{Simple Interest Earned} \\\\ I = Prt\qquad \begin{cases} I=\textit{interest earned}\dotfill&2,625\\ P=\textit{original amount deposited}\dotfill & \$25,000\\ r=rate\to 3.5\%\to \frac{3.5}{100}\dotfill &0.035\\ t=years \end{cases} \\\\\\ 2625=(25000)(0.035)t\implies \cfrac{2625}{(25000)(0.035)}=t\implies 3=t[/tex]
Answer:
The number of years = 3 years
Step-by-step explanation:
Points to remember
Simple interest
I = PNR/100
Where P - Principle amount
N - Number of years
R - Rate of interest
To find the number of years
Here P = 25,000
R = 3.5% and I = 2625
I = PNR/100
N = (I * 100)/PR
= (2625 * 100)/(25000 * 3.5)
= 3 years
Therefore number of years = 3 years
find the permiter of the polygon PLEASE help
Check the picture below.
Answer:
P = 46cmStep-by-step explanation:
If the circle inscribed in a quadrilateral, then the sums of the opposite sides of the quadrilateral are the same.
Therefore we have the equation:
AB + CD = BC + AD
Therefore the perimeter of polygon ABCD is equal to
P = 2(AB + CD)
Substitute AB = 10.5cm, CD = 12.5cm:
P = 2(10.5cm + 12.5cm) = 2(23cm) = 46cm
(7-c)(-1)
Simplify the expression
I’ve been stuck on this for a while now and I can’t get through it can someone please help me please
Answer:
-7 +c
Step-by-step explanation:
(7-c)(-1)
Distribute the -1
-1*7 -1*(-c)
-7 +c
stan cut two pieces of crown molding for his family room that were 8 feet 7 inches and 12 feet 11 inches. what was the total length of the molding?
Answer:
The total length of the molding is 21 feet and 6 inches
Step-by-step explanation:
* Lets explain how to solve the problem
- The length of the two pieces are 8 feet 7 inches and 12 feet 11 inches
- Each foot has 12 inches
- Lets change the lengths of the two pieces to inch
# First piece 8 feet 7 inches
∵ 1 foot = 12 inches
∴ 8 feet 7 inches = 8 × 12 + 7
∴ 8 feet 7 inches = 96 + 7
∴ 8 feet 7 inches = 103 inches
# Second piece 12 feet 11 inches
∵ 1 foot = 12 inches
∴ 8 feet 7 inches = 12 × 12 + 11
∴ 8 feet 7 inches = 144 + 11
∴ 8 feet 7 inches = 155 inches
- To find the total length add the two answers
∴ The total length of the molding = 103 + 155 = 258 inches
- Divide the answer by 12 to change it to feet
∵ 258 ÷ 12 = 21.5 feet
- To change it to feet and inch multiply 0.5 feet by 12
∵ 0.5 × 12 = 6 inches
∴ The total length of the molding is 21 feet and 6 inches
a diagnol of a cube measures 15 cm and the length of an edge is 75 square root.What is the length of the diagnol of a face of the cube? Round to the nearest tenth
A. 7.1
B. 12.2
C. 13
D. 15
Answer:
B: 12.2cm
Step-by-step explanation:
Got it right on edge 2021✅
What is the equation of a line that passes through the point (0, -2) and has a slope of -3?
Answer: Y = -3x-2
Step-by-step explanation:
if there are two co-ordinates (x1,y1) and (x2,y2).
If the line is passing through these co-ordinates
Then Slopw of the line = (y2-y1)/(x2-x1)
We have one co-ordinate (-0,-2) let it be (X1,Y1)
Let second co-ordinate be (X,Y)
Slope = -3 = (Y-(-2)) / (X-0)
-7 = (Y+2)/(X)
Y+2 = -3 (X)
Y+2 = -3X
ADDING -2 ON BOTH SIDES OF THE EQUATION
Y+2-2 = -3X-2
Y = -3x-2
Perform the indicated operation.
g(t) = 2t + 2
h(t) = t^2 - 2
Find (g•h)(-3)
A.62
B.14
C.16
D.126
Answer:
C
Step-by-step explanation:
Substitute t = - 3 into h(t), then substitute value obtained into g(t)
h(- 3) = (- 3)² - 2 = 9 - 2 = 7, then
g(7) = (2 × 7) + 2 = 14 + 2 = 16 → C
How much more will the total cost of three adult tickets be than three children tickets? (SHOW WORK) (Table at bottom)
Book Exhibition
Ticket | Cost
Adults | $22
Children | $15
Seniors | $14
Step-by-step explanation:
cost of adult ticket, AT = $22
Cost of child ticket, CT = $15
Difference in price, D = AT-CT = 22-15 =$7
Difference in price for 3 tickets = 3D = $21
Answer:
Three Adult Tickets will be $22 more than Three Children's Ticket
Step-by-step explanation:
One Adult= $22
One Child =$15
Three adults= $22 x 3= $66
Three Children= $15 x 3= $45
$66 - $45= $21
Identify if the proportion is true or false. 4 to 11 = 12 to 33.
Answer:
True
Step-by-step explanation:
Take 4/11 and you get 0.363636363636, which is the same if you take 12/33. So the proportion of the two is the same.
Answer:
True
Step-by-step explanation:
To find out if the proportion is true you have to find out what multiplied by 4 equals 12.
To find that out you have to divide 12 by 4 which equals 3.
Now you have to do the same for the denominators. So, 33/11 equals 3.
The proportion is true because the numerator and denominator are both multiplied by 3 to get 12 to 33.
Which of the following is equivalent to 3 sqrt x^5y
Answer:
[tex]\large\boxed{x^\frac{5}{3}y^\frac{1}{3}}[/tex]
Step-by-step explanation:
[tex]\text{Use}\ \sqrt[n]{a^m}=a^\frac{m}{n}\ \text{and}\ \sqrt[n]{ab}=\sqrt[n]{a}\cdot\sqrt[n]{b}\\\\\\\sqrt[3]{x^5y}=\sqrt[3]{x^5}\cdot\sqrt[3]{y^1}=x^\frac{5}{3}y^\frac{1}{3}[/tex]
Answer:
B
Step-by-step explanation:
edge 2021
Use a half-angle identity to find the exact value of tan 165 degrees
Answer:
√3 - 2.
Step-by-step explanation:
Let A = 330 degrees so A/2 = 165 degrees.
tan A/2 = (1 - cos A) / sin A
tan 165 = (1 - cos 330) / sin 330
= (1 - √3/2) / (-1/2)
= -2(1 - √3/2)
= -2 + 2 * √3/2
= √3 - 2.
Answer:
[tex]\sqrt{3}[/tex] - 2
Step-by-step explanation:
Using the half- angle identity
tan( [tex]\frac{x}{2}[/tex] ) = [tex]\frac{sinx}{1+cosx}[/tex]
[tex]\frac{x}{2}[/tex] = 165° ⇒ x = 330°
sin330° = - sin30° = - [tex]\frac{1}{2}[/tex]
cos330° = cos30° = [tex]\frac{\sqrt{3} }{2}[/tex]
tan165° = [tex]\frac{sin330}{1+cos330}[/tex]
= [tex]\frac{-\frac{1}{2} }{1+\frac{\sqrt{3} }{2} }[/tex]
= - [tex]\frac{1}{2}[/tex] × [tex]\frac{2}{2+\sqrt{3} }[/tex]
= - [tex]\frac{1}{2+\sqrt{3} }[/tex]
Rationalise by multiplying numerator/ denominator by the conjugate of the denominator
The conjugate of 2 + [tex]\sqrt{3}[/tex] is 2 - [tex]\sqrt{3}[/tex], hence
tan 165°
= - [tex]\frac{2-\sqrt{3} }{(2+\sqrt{3})(2-\sqrt{3}) }[/tex]
= - [tex]\frac{2-\sqrt{3} }{4-3}[/tex]
= - (2 - [tex]\sqrt{3}[/tex] )
= - 2 + [tex]\sqrt{3}[/tex] = [tex]\sqrt{3}[/tex] - 2
1452 divided by 44 = (1452 divided by 4) divided by 11
This division problem uses the method of...
A. Fractions
B. Repeated Subtraction
C. Factors
D. The Distributive Property
Answer:
Option C is correct.
Step-by-step explanation:
We are given
1452 divided by 44 = (1452 divided by 4) divided by 11
We know that 44 = 4*11
So, 4 and 11 are factors of 44.
This division problem uses the method of Factors.
Option C is correct.